Analisis Potensi Pengembangan Pasar Kerajinan Amuntai Kabupaten Hulu Sungai Utara sebagai Destinasi Wisata - Siska Fitriyanti (Jurnal Kebijakan Pembangunan, 2020)
Amuntai Craft Market in Hulu Sungai Utara Regency is a market that is unique and has potential as a tourist destination. This market sells a variety of handicrafts made from purun and rattan which are produced by local craftsmen. To improve the economy of the community and the region, the Amuntai Craft Market needs to be developed optimally so that it can become a tourist destination. This paper aims to analyze the potential for developing the Amuntai Craft Market as a tourist destination in terms of its strengths, weaknesses, opportunities, and external challenges. This paper is a descriptive exploratory. Primary data were collected through field observations, interviews with local government in charge of market affairs, and interviews with artisans. Secondary data obtained through interviews with relevant parties and literature relevant to the topic of writing. Data were analyzed using the SWOT method, which was then reduced to a recommendation for a strategic step for market development. The analysis shows that the Amuntai Craft Market has great potential to be developed as one of the tourist destinations because it has the uniqueness of handicraft products, and the products are well-liked for the design of goods and affordable prices, and the availability of human resources that have been hereditary producing handicraft products. The weaknesses of the Amuntai Craft Market are that they do not have permanent buildings, market time is very limited so that it is difficult to access by visitors outside the regency, there is no standard of quality and price of the product, and there is a lack of management from the local government. Recommendations for market development are the promotion of market presence, enhancing the competitiveness of handicraft products through training and coaching, market relocation to be accessible to visitors outside the region every day. Keywords: Amuntai Craft Market, Tourism, SWOT ABSTRAK Pasar Kerajinan Amuntai merupakan pasar yang memiliki keunikan dan berpotensi sebagai destinasi wisata. Pasar ini khusus menjual berbagai barang kerajinan yang diproduksi oleh para pengrajin lokal. Tulisan ini bertujuan untuk menganalisis potensi pengembangan Pasar Kerajinan Amuntai sebagai destinasi wisata. Tulisan ini bersifat deskriptif eksploratif. Data primer diambil melalui observasi lapangan dan wawancara. Data dianalisis menggunakan metode SWOT, yang kemudian diturunkan menjadi rekomendasi langkah strategis pengembangan pasar. Hasil analisis menunjukkan bahwa kekuatan Pasar Kerajinan Amuntai terletak pada kekhususan menjual produk kerajinan, desain barang selalu ada pembaruan, harga terjangkau, dan ketersediaan SDM yang telah turun temurun memproduksi barang kerajinan. Adapun kelemahannya adalah tidak memiliki bangunan permanen, waktu operasional pasar sangat terbatas sehingga sulit diakses oleh pengunjung dari luar daerah, serta belum memiliki standar kualitas dan standar harga. Rekomendasi untuk pengembangan pasar adalah relokasi ke tempat yang telah disediakan oleh pemerintah daerah, penyesuaian waktu operasional pasar untuk memperluas akses pengunjung luar daerah, serta pembinaan dan pendampingan kontrol kualitas produk. Kata Kunci: Pasar Kerajinan Amuntai, Pariwisata, SWOT